Chemical Imaging and Analysis of Single Nerve Cells by Secondary Ion Mass Spectrometry Imaging and Cellular Electrochemistry - Lork, Alicia A.; Vo, Kim L. L.; Phan, Nhu T. N. (Frontiers in Synaptic Neuroscience, 2022)
Nerve cell, a unit of neuronal communication in a nervous system, is a heterogeneous molecular structure which is highly mediated to accommodate cellular functions. Understanding the complex regulatory mechanisms of neural communication at the single cell level requires analytical techniques with high sensitivity, specificity and spatial resolution. The challenging technologies for chemical imaging and analysis of nerve cells will be described in this review. Secondary ion mass spectrometry (SIMS) allows non-targeted and targeted molecular imaging of nerve cells and synapses at sub-cellular resolution. Cellular electrochemistry is well suited for quantifying the amount of reactive chemicals released from living nerve cells. These techniques will also be discussed regarding multimodal imaging approaches which have recently been shown to be advantageous for the understanding of structural and functional relationships in a nervous system. This review aims to provide an insight of the strengths, limitations, and potentials of these technologies for synaptic and neuronal analysis.